Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2010)
Turnover rate of tear-film lipid layer determined by fluorophotometry Mochizuki H, Yamada M, Hatou S, Tsubota K Br J Ophthalmol 2009: 93: 1535-38. Cataract surgery and primary intraocular lens implantation in children <2 years old in the UK and Ireland: finding of national surveys Solebo AL, Russell-Eggitt I, Nischal KK, Moore AT, Cumberland P, Rani JS, B.J Ophthalmol 2009; 93: 1495-1498. Predicting visual success in macular hole surgery Gupta B; Laidlaw DAH, Williamson TH, Shah SP, Wong R, Wren S B.J Ophthalmol 2009; 93: 1488-1491. Aqueous Vascular Endothelial growth factor as a predictor of macular thickening following cataract surgery in patients with diabetes mellitus Hartnett ME, Tinkham N, Paynter L, Geisen P, Rosenberg P, Koch G, Cohen KL Am J Ophthalmol 2009; 148: 895-901.